(untitled) (University of Khartoum Engineering Journal, 2022)
Aligning employees with the organization’s strategic goals has become increasingly important as organizations strive to achieve the optimum levels in organizational performance, profitability and business sustainability. The aim of this study was to reveal the main barriers in the alignment process between employees’ objectives and the organizational goals in a governmental corporation. Secondly, to propose a suitable and applicable course of action for better organizational alignment. To achieve optimum results; both qualitative and quantitative research methods (detailed questionnaire and personal interviews) have been applied in this paper. Gathered data have been analyzed by spread sheets and web-based models such as Google forms. The results show that there is a lack of effective communication throughout the corporation, knowledge and capabilities are not developed, employees are not involved or empowered, and finally people efforts are not rewarded or recognized. Furthermore, the results illustrate the satisfactory factors that affect employees’ job performance and achieve the highest level of motivation. The recommended action plan in this paper is based on information gathered through an extensive literature review, and researcher experience in this field. This study is an attempt to establish the basic criteria to enhance leadership credibility, minimize wasted resources, and achieve the optimum utilization of human resources in the governmental sector.